1994
DOI: 10.1152/ajpendo.1994.266.4.e666
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of a mixed meal by the conscious dog

Abstract: The disposition of a mixed meal administered intragastrically was examined in 13 24-h-fasted conscious dogs, using the arteriovenous (AV) difference technique (and isotopic methods in 6 dogs). Postprandial net gut output totaled (in g of glucose equivalents) 42 +/- 6 glucose, 3 +/- 0.3 lactate, 2 +/- 0.2 alanine, and 0.2 +/- 0.0 glycerol. The gut oxidized 2 +/- 1 g of glucose, and 0.2 +/- 0.1 g remained within the intestinal lumen. Of the administered glucose 68 +/- 6% were accounted for, and volatile fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 20 publications
2
33
0
1
Order By: Relevance
“…The lower arterial glucose levels likely contributed to the lower insulin levels. Consistent with previous studies, only ϳ70% of the glucose given enterally is absorbed as glucose (8,17); the remaining 30% is metabolized by the intestine. A failure to absorb 100% of the enterally delivered glucose as glucose is likely not the sole explanation for the lower insulin concentration in TPNϩEG.…”
Section: Discussionsupporting
confidence: 90%
“…The lower arterial glucose levels likely contributed to the lower insulin levels. Consistent with previous studies, only ϳ70% of the glucose given enterally is absorbed as glucose (8,17); the remaining 30% is metabolized by the intestine. A failure to absorb 100% of the enterally delivered glucose as glucose is likely not the sole explanation for the lower insulin concentration in TPNϩEG.…”
Section: Discussionsupporting
confidence: 90%
“…Knowing that the insulinbrain-liver signaling axis was intact in dogs, we undertook a second set of experiments to determine whether a physiologic increase in brain insulin could activate central signaling and thereby modify hepatic glucose metabolism in vivo. To this end, we brought about an increase in brain insulin that was physiologic in both its route of administration (infused into the arteries that perfuse the brain) and its magnitude (~10-fold increase), the latter being within the physiologic range of arterial hyperinsulinemia seen after a mixed meal (26). In order to allow the impact of such a change to be clearly seen, we maintained basal insulin and glucagon levels at the liver.…”
Section: Discussionmentioning
confidence: 99%
“…The liver is an important site of glucose removal after a meal (1,8,13,18,33,37,38). Several studies have demonstrated that the combination of hyperglycemia, hyperinsulinemia, and intraportal glucose infusion (portal signal) can produce rates of NHGU that are comparable with rates observed after glucose ingestion (32,39,40).…”
Section: Discussionmentioning
confidence: 99%